Examining Intrinsic Motivation and Job Satisfaction among Academic Staff at Svay Rieng University in Cambodia - PEN, Dina (Journal of General Education and Humanities, 2024)
This study examines the intrinsic motivation level of academic staff at Svay Rieng University (SRU) and its relationship with job satisfaction. To understand what keeps these academicians from doing what they do, it is essential to research to establish the level by which achievement, recognition, work itself, responsibility, advancement, and growth intrinsically motivate them as they dispose of their daily functions as academic staff. A quantitative survey was conducted on 91 SRU academic staff. The main findings revealed a positive and significant correlation between intrinsic motivation and job satisfaction. The staff members exhibit high intrinsic motivation, but variations exist across different aspects of their work. They express a need for increased recognition and praise. To enhance intrinsic motivation and job satisfaction, it is recommended to implement recognition and reward policies, provide professional development support, and foster a supportive work environment. Involving staff in decision-making, conducting research-driven policy development, and monitoring and improving the work environment are vital. Additional measures include implementing flexible work policies, establishing regular feedback systems, creating recognition programs, and developing learning and development policies. Future research should explore the relationship between intrinsic motivation and other outcomes.